PEMBERIAN PROGRAM SPECIAL IMMIGRANT VISA AMERIKA SERIKAT BAGI WARGA NEGARA AFGHANISTAN TAHUN 2009-2014 - Indraswari, Desak Ketut; Dharmiasih, D.A Wiwik; Nugraha, A.A. Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
9/11 brought a considerable impact on international security, especially for United States. Post 9/11, US declared Global War on Terrorism and war in Afghanistan to arrest the perpetrators of 9/11. US also made changes in their immigration policy. This research analyzes the purpose of US in providing Special Immigrant Visas (SIV) program for citizens of Afghanistan in 2009-2014. SIV program is certainly contradictory with US’s policy post 9/11. This issues discussed by answering the question to why the US provide SIV for citizens of Afghanistan. Data for this study were collected from various sources including: literary sources, news and reports, thenanalyzed with national interest, national strategic and foreign policytheoriticalframeworks. The analysis shows that US provide SIV program to recruit citizens of Afghanistan in achieving the US’s goals on Afghanistan war. SIV program serves as an attraction and appreciation of Afghan citizens who have helped US in Afghan war. Keywords: Terrorism, Special Immigrant Visa, National Interest, National Strategy, Foreign Policy